AB1336-HPR NON-PHARMACOLOGIC TOPICS RELEVANT FOR CLINICAL RESEARCH IN RHEUMATIC DISEASES: THE PATIENT PERSPECTIVE. (2nd June 2020) - Ingegnoli, F.; Schioppo, T.; Ubiali, T.; Ostuzzi, S.; Buoli, M.; Bollati, V.; Caporali, R.
Abstract : Background: The research approach on Rheumatic diseases (RDs) is challenging and patient involvement as partners in medical research is an emerging force to obtain relevant information and to add unique skills, values and experiences to research. Despite growing interest in non-pharmacologic aspects of clinical research in RDs, the patients' perspective is currently poorly explored. Objectives: To identify and rank the priorities for clinical research according to patients' perspective. Methods: A structured face-to-face meeting between physicians and a patient representative was convened to list the non-pharmacologic topics relevant to RD patients. A cross-sectional no-profit on-line anonymous survey was devised to evaluate opinions of RD patients. They were asked to rate the following topics: food/nutrition, air pollution, smoking, work activity, social participation, physical activity, emotional well-being/stress, alternative medicine, and patient-physician relationship. Moreover, patients were asked to explain for which reason a topic was considered important (disease prevention, halting disease progression, symptoms control and disease cure). The survey was disseminated by ALOMAR (Lombard Association for Rheumatic Diseases) between June and October 2019. Results: 200 rheumatic patients completed the survey: 130 inflammatory arthritis, 50 connective tissue diseases/vasculitis, and 20 among osteoarthritis, gout, condrocalcinosis, polymyalgia and primary fibromyalgia. Respondents were 178 female with median age of 50 years and median disease duration of 7 years. Among the nine topics identified, the one most rated by patients was the doctor-patient relationship; 188 (94%) of respondents considered this topic very or extremely important (see table below). In descending order, patients rated very or extremely important: psychological well-being/stress 185 (92.5%), physical activity 155 (77.5%), nutrition, eating habits and alcohol 150 (75%), alternative therapies 144 (72%), work activity 144 (72%), environmental pollution 134 (67%), social life 121 (60.5%) and cigarette smoke 119 (59.5%). The topics considered relevant was perceived to be able to influence disease symptoms. Regarding RD prevention, environmental pollution and cigarette smoking were considered the most important topics, while fewer patients believed that research on other topics could help to stop disease progression or to achieve disease healing. Conclusion: This survey highlights the relevance of several unmet needs. The holistic approach, in terms of medical consultation and psychological well-being, is considered the most important component able to influence disease perception. By capturing patient opinions on non-pharmacological topics for clinical research, this survey indicates that the active patient involvement is essential to design successful translational studies and improve clinical outcomes. Acknowledgments: We thank the Lombard Association of Rheumatic Diseases (ALOMAR) for its contribution to plan and disseminate the survey and the group that sustain systemic sclerosis (GILS). Disclosure of Interests: Francesca Ingegnoli: None declared, Tommaso Schioppo: None declared, Tania Ubiali: None declared, Silvia Ostuzzi: None declared, Massimiliano Buoli: None declared, Valentina Bollati: None declared, Roberto Caporali Consultant of: AbbVie; Gilead Sciences, Inc.; Lilly; Merck Sharp & Dohme; Celgene; Bristol-Myers Squibb; Pfizer; UCB, Speakers bureau: Abbvie; Bristol-Myers Squibb; Celgene; Lilly; Gilead Sciences, Inc; MSD; Pfizer; Roche; UCB